ANTIBACTERIAL SUSCEPTIBILITY PROFILE OF ESCHERICHIA COLI IN A PRIVATE HOSPITAL, INDIA : Pharmaceutical Sciences-Pharmacy practice - CHANDRASEKARAN, K.; D, GANDHIRAJ.; PRASAD MOHANTA, GURU; RAJASEKARAN, A. (International Journal of Life Science and Pharma Research, 2018)
E.coli is a freely available gram negative bacteria among the natural resources like gut of animals which at the same time emerges to be one of the most causative organisms for stomach and urine related infections in humans. The presence of Extended-spectrum beta-lactamase ESBL type of drug resistance is constantly evolving and are under dynamic flux posing a global threat to public health programs. Also, there is a significant necessity for regular antimicrobial sensitivity surveillance not only for the presence and spread of ESBL genes but also for both urban and rural populations for more informed and structured treatment.At an institutional level, practices that can minimize the spread of such organisms include clinical and bacteriological surveillance of patients admitted to intensive care units and antibiotic cycling, as well as policies of restriction, especially on the empirical use of broad-spectrum antimicrobial agents. The present study focuses on the trends of antibacterial susceptibility and resistance among clinically isolated E.coli for rational prescribing. Susceptibility and resistance data of E.coli were collected from a tertiary care hospital’s Microbiology Department over a period of three years. The data collected included patient’s source (ICU or ward), specimen of the isolate, antibacterial susceptibility and resistance profile. E.coli was identified from the sample on the basis of colony and microscopic morphology. Commercially available antibiotic disks were used for antimicrobial susceptibility testing as per Kirby–Bauer disk diffusion method and Clinical Laboratories Standard Institute CLSI guidelines.The pattern of antibiotics used within prescribing pattern for E.coli were found out to be 33.3%, 30.3% and 27.5% in the study period. The identification of EBSL, AmpC, Carbapenamase were carried out as they were identified to be as resistant strains and more complicated in terms of identification and treatment.Susceptibility to third generation Cephalosporins, Gentamycin, Imipenem,Meropenem, Amikacin showed a narrow increase in resistance level against E. coli.